2008
DOI: 10.1002/col.20434
|View full text |Cite
|
Sign up to set email alerts
|

Color preference of aged observers compared to young observers

Abstract: In modern society, elderly people tend to become enthusiastic users of displays. These displays are optimized for the visual properties of young adults ignoring the specific attributes of the vision of the elderly though the existence of differences is evident. It is true, however, that most of the investigations follow a bottomup paradigm (changes of optical density, neural changes, etc.), and their results are too ambiguous to be taken into account directly in display optimization for the elderly, partly bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 20 publications
3
36
0
1
Order By: Relevance
“…For contrasts involving the very red poppy field (compared to the fern forest or the fruit bowl), the older participants reported that a relatively higher saturation made the poppy field look correct. This is consistent with the imaging literature . Here too we might have had a stronger result with a larger sample of older participants.…”
Section: Discussionsupporting
confidence: 91%
“…For contrasts involving the very red poppy field (compared to the fern forest or the fruit bowl), the older participants reported that a relatively higher saturation made the poppy field look correct. This is consistent with the imaging literature . Here too we might have had a stronger result with a larger sample of older participants.…”
Section: Discussionsupporting
confidence: 91%
“…The complexity of elements in the design of the particular environment greatly influences the individual's color perception. Furthermore, the age of the observer is also of interest because findings from studies indicate that color preference changes with an individual's age (Beke et al 2008;Milne and Greenway 1999;Zentner 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the results of most of the color studies have been done in laboratory or testing room, or using color samples and simulated images in articles, or computer programs with color samples or other color elements . Nevertheless, few studies have combined the method assessment with an actual setting context in order to evaluate the effects of participants in this context .…”
Section: Resultsmentioning
confidence: 99%